EFFECT OF MULTIMEDIA UTILIZATION AND LEARNING STYLE TOWARD PRESTATION OF SOCIAL STUDIES (Experiment Study At Class VI Of State Unior High School 1 Rejang Lebong Regency) - Zamhari Zamhari; Riyanto Riyanto (DIADIK, 2019)
The aims of this research to know; 1) a significant or no different between social study result at learning media experiment class,  and the globe dan map at 7th class social study learning, Unior High School 1 Rejang Lebong Regency.2) a significant or no different between social study prestation which have visual and auditory learning style at 7th class social study learning, Unior High School 1 Rejang Lebong Regency, 3) a significant or no different between learning media toward social study prestation at 7th class social study learning, Unior High School 1 Rejang Lebong Regency. In this research which is used experimental research design Two Ways Anava. Data collection technique used questionaire and test. This research uses a quantitative approaching, data collection technique used questionnaire and test    to    find    out    the     learning    media utilization and learning style toward prestation of social studies. To examines the research's hypothesis is using T-test analysis and Variancy Two Ways by calculates the instrument validity eachvariabels. The research's result shows there are: (1) a significant influence between learnign media utilization, and learning style toward prestation of social studies, (2) no different significant influecnce prestation of social studies which have visual and auditory learning style. (3) no different significant influence the learning media utilizationand learning style toward prestation of social studies